Evaluation of temperature and osteotomy speed with piezoelectric system - Marques, Ana C. [UNESP]; Lopes, Guilherme R. [UNESP]; Samico, Renata P. [UNESP]; Matos, Jefferson D. [UNESP]; Souza, Francisley A.; Corat, Evaldo J.; Nishioka, Renato S. [UNESP] (Edizioni Minerva Medica, 2021)
BACKGROUND: Piezosurgery is an option to realize several clinical and surgical procedures, due to its advantages as precision in osteotomy. This study aims to evaluate the heating and osteotomy speed in bone blocks of ox’s shins, to report the best way of its use in the clinical practice. METHODS: A bone blocks had the dimensions as follow: 20 mm length, 10 mm width, and 5 mm wide. It was evaluated 5 different groups: group LM (low speed and medium pressure); group HM (high speed and medium pressure); group HH (high speed and high pressure); group LH (low speed and high pressure); group LL (low speed and low pressure). The heating increasement was measured with a thermal viewer and the osteotomy was timed when the cut depth reached 5 mm and the whole block detached itself. One-way ANOVA and Tukey tests were adopted to analyze the data and the level of significance was set at a P value of 0.05. RESULTS: The pressure and speed of the tip, works directly in the generated temperature during osteotomy. The medium pressure level is the most favorable, because high pressure level caused a high increase in heating over the bone and low pressure presented a very long osteotomy time. CONCLUSIONS: The high speed and medium pressure can be suggested as the most efficient in both standards of time/ temperature to realize the osteotomy.
Keywords: Bone; Bones; Piezosurgery; Temperature